TEACHING STRATEGIES TO ENGAGE LEARNERS IN ACTIVE LEARNING IN BUSINESS STUDIES - Ngwenya Jabulisile,; Zulu Sphelele, (International Journal of Innovative Technologies in Social Science, 2023)
Teachers in the 21st century are encouraged to creatively and actively engage learners in the learning process. This requires teachers to use student-centred approaches for learners to improve their learning experiences This article explores teaching strategies teachers use to engage learners in active learning in Business Studies. The study employed a qualitative case study of six purposively selected Grade 10 Business Studies teachers. Data were obtained through semi-structured individual and focus group interviews. Thematic analysis method was used to analyse data. What emerged from the findings is that participants acknowledged the role of learner involvement in creating a supportive social environment that allowed opportunities for enhancing learning of new concepts. Teachers were inspired to express themselves and share in a more relaxed manner without being ridiculed during discussions and presentations. Engaging learners in a variety of collaborative activities led to positive interdependence and interaction while developing self-confidence and interpersonal skills. Diversity in members created spaces for learners to share different viewpoints.